2021
DOI: 10.2514/1.j058407
|View full text |Cite
|
Sign up to set email alerts
|

Flow Enthalpy of Nonequilibrium Plasma in 1 MW Arc-Heated Wind Tunnel

Abstract: The flow enthalpy of an arc-heated wind tunnel is an important parameter for reproducing planetary entry and performing heating tests. However, its distribution is insufficiently clarified owing to complicated phenomena, such as arc discharge and supersonic expansion. In this study, we assess the enthalpy of an arc-heated flow in a large-scale facility based on measurements and computational results. The flow enthalpy of high-temperature gases, which comprised thermal, chemical, kinetic, and pressure component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The test model with a diameter of 50 mm was located at x = 150 mm. A previous study [35] reported that strong thermal nonequilibrium is also observed inside the nozzle, where the electron temperature and vibrational temperature at the nozzle exit (x = 0 mm) are higher than the translational and rotational temperatures. This trend was the same as that of the free jet in the test chamber.…”
Section: Shock Layer Structurementioning
confidence: 88%
See 4 more Smart Citations
“…The test model with a diameter of 50 mm was located at x = 150 mm. A previous study [35] reported that strong thermal nonequilibrium is also observed inside the nozzle, where the electron temperature and vibrational temperature at the nozzle exit (x = 0 mm) are higher than the translational and rotational temperatures. This trend was the same as that of the free jet in the test chamber.…”
Section: Shock Layer Structurementioning
confidence: 88%
“…For each, we calculated the mean value and standard deviation from the rotational temperature result obtained by spectral fitting. The determination of the rotational temperature of the free jet spectra is described in reference [35]. The NO rotational temperature in the shock layer was 6620 ± 350 K; this is higher than the free jet rotational temperature of 770 ± 60 K. This is because the translational temperature first increases due to the flow stagnation across the shock wave, following which the rotational temperature increases owing to the energy relaxation process from the translational to the rotational degrees of freedom.…”
Section: Measured Rotational Temperaturementioning
confidence: 97%
See 3 more Smart Citations